Preservation of Local Wisdom in Lemah Ireng Village - Noviana, Eka; Rinenggo, Alil; Puji, Novi Sucining; Arviani, Adip Vasya; Pratomo, Merian (Pancasila and Civics Education Journal, 2022)
Local wisdom is part of culture that cannot be separated from society. One of the local wisdoms in the form of traditions that still survive is in Lemah Ireng Village. This research is motivated by the low awareness of the nation's children, especially the youth of the current generation of culture. This study aims to find out local wisdom that still exists and how the community preserves traditions or customs. The research uses a qualitative approach. Data collection techniques through interviews and observation. Data analysis went through four stages, namely data collection, data presentation, data reduction, and drawing conclusions. The results of this study indicate that the local wisdoms that are still being preserved in Lemah Ireng Village are the Punggahan tradition, Pudunan tradition, and Sedekah Bumi. Preservation of local wisdom is carried out by teaching the younger generation to recognize, learn, and be involved in the traditions or customs that exist in Lemah Ireng Village. The community hopes that the prevailing customs will not be lost and continue to develop into the next generation.